Relative Roles of Inhibin B and Sex Steroids in the Negative Feedback Regulation of Follicle-Stimulating Hormone in Men across the Full Spectrum of Seminiferous Epithelium Function - Boepple, Paul A. (The Endocrine Society, 2008)
Context and Objective: Our aim was to explore the relative roles of gonadal sex steroids and inhibin B in the regulation of FSH across a spectrum of seminiferous epithelium function. Subjects: The study included three groups: group I, healthy men (n = 31); group II, men with idiopathic hypogonadotropic hypogonadism receiving pulsatile GnRH (n = 12) selected to represent a spectrum of seminiferous tubular development, testicular size, and baseline inhibin B levels; and group III, men with functional anorchia (n = 3) receiving testosterone replacement. Design: Subjects were studied before and after 3 d of acute sex steroid withdrawal. Setting: The study was conducted at the Mallinckrodt General Clinical Research Center of Massachusetts General Hospital. Interventions: Acute biochemical castration was achieved using high-dose ketoconazole (groups I and II) or withdrawal of androgen therapy (group III). Main Outcome Measures: The relationship between FSH and inhibin B in both normal and castrate sex steroid milieu was measured. Results: In both normal and castrate sex steroid milieus, there was a negative relationship between inhibin B and FSH, best described by a logarithmic model. Acute biochemical castration resulted in the most dramatic increases in FSH in men with the lowest baseline inhibin B levels. Conclusions: We came to the following conclusions: 1) in the human male, inhibin B is the principal gonadal feedback regulator of FSH secretion unless seminiferous tubular function is severely compromised, and a logarithmic model best describes this relationship; and 2) sex steroid inhibition of FSH secretion is most apparent when serum inhibin B levels fall well below the normal range.